2016
DOI: 10.1016/j.jcin.2016.02.014
|View full text |Cite
|
Sign up to set email alerts
|

1-Year Results of Paclitaxel-Coated Balloons for Long Femoropopliteal Artery Disease

Abstract: Paclitaxel-coated balloons are associated with favorable functional and clinical outcomes at 1 year in patients with long femoropopliteal artery disease requiring percutaneous revascularization. (Drug Eluting Balloon [DEB] and Long Lesions of Superficial Femoral Artery [SFA] Ischemic Vascular Disease [DEB-SFA-LONG]; NCT01658540).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 21 publications
3
54
0
1
Order By: Relevance
“…In 104 patients (110 lesions) with a mean lesion length for DCB of 94 ± 60 vs. 96 ± 69 mm for PTA, the primary endpoint (1‐year restenosis) was lower in the DCB group (17% vs. 47.3%); P = 0.008). Registry data supports the effectiveness of DCBs in long femoral‐popliteal disease (> 15 cm) reporting that 105 consecutive patients with RC 2 to 4 and a treated lesion length of 25 ± 7 cm obtained a 1‐year patency rate of 83.2% with only 11% requiring bailout stents .…”
Section: Methodssupporting
confidence: 57%
“…In 104 patients (110 lesions) with a mean lesion length for DCB of 94 ± 60 vs. 96 ± 69 mm for PTA, the primary endpoint (1‐year restenosis) was lower in the DCB group (17% vs. 47.3%); P = 0.008). Registry data supports the effectiveness of DCBs in long femoral‐popliteal disease (> 15 cm) reporting that 105 consecutive patients with RC 2 to 4 and a treated lesion length of 25 ± 7 cm obtained a 1‐year patency rate of 83.2% with only 11% requiring bailout stents .…”
Section: Methodssupporting
confidence: 57%
“…39 The rates of provisional stenting among DCB treated FP lesions range from 4.1% to 27% in clinical trials and from 11% to 23.3% in two real-world studies from Italy and Germany respectively. 33,38,[40][41][42] Bail-out stenting was 14.2% in our DCB treated FP lesions, while the total rate of adjunctive stenting (bail-out or planned) was 31%. These rates are higher than those reported by the clinical trials.…”
Section: Discussionmentioning
confidence: 76%
“…Both of these trials included patients with moderate length (e.g., <15cm) lesions, but recent observational data suggest that DCB angioplasty is also effective in longer, more complex femoropopliteal lesions. In a study of 105 patients with TASC type C and D lesions, DCB angioplasty demonstrated a primary patency rate of 83% at 1 year . These findings are superior to rates of primary patency reported for drug‐eluting stents (78%), nitinol stents (49%), and covered self‐expanding stents (67%) in similar femoropopliteal lesions .…”
Section: Discussionmentioning
confidence: 86%